2021
DOI: 10.1182/bloodadvances.2020003605
|View full text |Cite
|
Sign up to set email alerts
|

Secondary cytogenetic abnormalities in core-binding factor AML harboring inv(16) vs t(8;21)

Abstract: Patients with core-binding factor (CBF) acute myeloid leukemia (AML), caused by either t(8;21)(q22;q22) or inv(16)(p13q22)/t(16;16)(p13;q22), have higher complete remission rates and longer survival than patients with other subtypes of AML. However, ∼40% of patients relapse, and the literature suggests that patients with inv(16) fare differently from those with t(8;21). We retrospectively analyzed 537 patients with CBF-AML, focusing on additional cytogenetic aberrations to examine their impact on clinical outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 40 publications
7
30
3
Order By: Relevance
“…By following this new rule, at least one structural ACA and another numerical ACA are required to define a complex karyotype, which, in turn, did show negative prognostic impact in our previous study [32]. This hypothesis is also supported by Mosna et al [33] and Han et al [28], who suggested that a complex karyotype, if defined by the presence of >= 4 chromosomal abnormalities, is associated with adverse survival in patients with inv(16)/t(16;16) AML. Further investigation is needed to explore the association between ACAs, especially structural ACAs, and prognosis in this cohort.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…By following this new rule, at least one structural ACA and another numerical ACA are required to define a complex karyotype, which, in turn, did show negative prognostic impact in our previous study [32]. This hypothesis is also supported by Mosna et al [33] and Han et al [28], who suggested that a complex karyotype, if defined by the presence of >= 4 chromosomal abnormalities, is associated with adverse survival in patients with inv(16)/t(16;16) AML. Further investigation is needed to explore the association between ACAs, especially structural ACAs, and prognosis in this cohort.…”
Section: Discussionsupporting
confidence: 73%
“…FISH testing played an important or even a decisive role in the exclusion of inv(16)/t(16;16) AML in all these scenarios. A confirmation of CBFB rearrangement and consequently the diagnosis of inv(16)/t(16;16) AML are decisive for the clinical management of the patients, e.g., whether to administer cytarabine-based intensive chemotherapy and the likelihood of a favorable response [3,[28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survival analysis of the study revealed different prognostic patterns of cytogenetic factors among the CBF AML subgroups: in inv( 16), chromosomal alterations other than +8 were associated with decreased OS, while trisomy 8 was associated with longer survival. Differently, in t(8;21), hypodiploidy was significant for DFS, whereas hyperdiploidy and del(9q) were associated with improved OS [33]. In the current molecular era, these results confirm the timeless relevance of conventional cytogenetic findings on CBF AML prognosis.…”
Section: Secondary Additional Chromosomal Abnormalitiesmentioning
confidence: 62%
“…The number of supplementary chromosome lesions, especially when they are more than 3, in line with other AML subgroups, is associated with a worse outcome [23], according to the prognostic risk scoring by Yoon et al [20]. Recently, Han et al [33] have retrospectively drawn up the largest cytogenetic dataset of CBF AML, therefore characterizing and differentiating the genomic features of the two AML subtypes. Trisomies of chromosomes 8, 21 or 22 recurred significantly more frequently in inv( 16)-bearing patients, in line with previous studies [6,8,19], such as hyperdiploidy.…”
Section: Secondary Additional Chromosomal Abnormalitiesmentioning
confidence: 99%